Decolonizing Public Speaking - de Cuba, Carlos; Seymour, Cheyenne; Slocum, Poppy (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2025)
This paper takes a critical approach towards public speaking assignments and courses that perpetuate colonial perspectives and values. We explore how standard language ideology creates disadvantages for students from marginalized language backgrounds while privileging Western communication norms. In this context, we investigate the tension between speaker authenticity and audience adaptation, particularly for diverse student populations navigating academic and professional contexts. The paper proposes concrete alternatives to behaviour-based assessment through outcomes-based rubrics and reflective self-assessment practices that honour linguistic and cultural diversity while maintaining academic rigor. By reimagining public speaking pedagogy through a decolonial lens, educators can create more equitable learning environments that value diverse communication styles without sacrificing effectiveness.